Gig Workers’ Performance through Work Motivation and Organizational Commitment: An Evidence of Gojek Drivers Surabaya - Moh Rivqi Amin (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2024)
This research aims to investigate the impact of work ethics, compensation, and work environment on work motivation, organizational commitment, and performance of gig workers in GOJEK Surabaya, Indonesia. The study involved 349 drivers of GOJEK Surabaya, selected through random sampling techniques, and Structural Equation Modeling (SEM) with the AMOS 21 program. The findings revealed that work ethics did not affect work motivation, organizational commitment, or work performance, while compensation did not affect work motivation or organizational commitment. Additionally, commitment did not affect work performance, whereas the work environment affected work motivation and organizational commitment, but not on work performance. Furthermore, work motivation did not affect work performance, and organizational commitment did not affect work performance. This study can assist the company in improving performance by providing excellent service to its consumers through gig workers.